Influence of Patient-Level Factors on Mode of Delivery among Operative Vaginal Delivery Candidates in Modern Practice - Metz, Torri D.; Gonzalez, Christina; Allshouse, Amanda A.; Henry, Erick; Esplin, Sean (American Journal of Perinatology, 2017)
Objective We aimed to evaluate which patient-level factors influence mode of delivery among candidates for operative vaginal delivery.Study Design Cross-sectional study of candidates for operative vaginal delivery from 18 hospitals over 8 years. Probabilities of mode of delivery were estimated using hierarchical logistic modeling adjusting for clustering within physician and hospital.Results Total 3,771 (64%) women delivered with forceps, 1,474 (25%) vacuums, and 665 (11%) cesareans. Odds of forceps versus vacuum were higher with induction (OR = 2.16, 95% CI: 1.76–2.65), nulliparity (OR = 2.06, 95% CI: 1.59–2.66), epidural (OR = 2.05, 95% CI: 1.19–3.56), maternal indication (OR = 1.53, 95% CI 1.16–2.02), older maternal age (OR 1.18, 95% CI 1.06–1.31 per 5 years), and longer second stage (OR = 1.10, 95% CI: 1.01–1.20 per hour).Odds of cesarean versus operative vaginal delivery were higher with maternal indication (OR = 9.0, 95% CI: 7.23–11.20), a perinatologist (OR = 2.51, 95% CI: 1.09–5.78), longer second stage (OR = 1.79, 95% CI: 1.65–1.93 per hour), older gestational age (OR = 1.10, 95% CI: 1.01–1.20 per week), and longer labor (OR = 1.02, 95% CI: 1.01–1.04 per hour).Conclusion Patient-level factors influence the decision to proceed with an operative vaginal delivery and the choice of instrument, thereby emphasizing the importance of maintaining availability of both forceps and vacuums.
Keywords: clinical characteristics; forceps; indication; operative delivery; vacuum